Effect of molecular-mass distribution on surface tension of oligomers - V. S. Kopytin; V. M. Komarov; A. N. Trofimov; I. D. Simonov-Emeljanov (Тонкие химические технологии)
Effect of molecular mass (MM) and molecular-mass distribution (MMD) on surface tension of oligomers has been investigated. Narrow fraction of polyethyleneglycols (from 300 to 40000) and their double and triple mixtures of different composition was used as model. Obtained results prove possibility of regulation surface tension of oligomers and polymers by changing MM and MMD and indicated that stability system’s behaviour increases with enlargement of MMD of oligomer mixtures.